Increasing interest in learning through the traditional paper crack game in primary school students - Kumala, Farida Nur; Aisah, Nur; Nita, Cicilia Ika Rahayu (Universitas Kanjuruhan Malang, 2024)
This research aims to increase students' interest in learning through the application of the traditional Ektas game media. The type of research used is Classroom Action Research (PTK). The subjects of this research were 27 students consisting of 13 male students and 14 female students. The data collection techniques used were observation techniques, interest questionnaires, field notes and documentation. Data analysis in this research is descriptive qualitative and descriptive quantitative. Based on the research results, the percentage of students' interest in learning increased rapidly from the results of observation measurements in cycle I of 71.92%, increasing in cycle II to 90.37%. This was also followed by an increase in the results of the questionnaire measuring interest in learning from 71.48% in cycle II to 90.40%. Based on the research results, it can be concluded that the traditional Ektas game media can increase students' interest in learning.